The teacher's personality becomes a role model for students - Royanto Siahaan; Dorlan Naibaho; Rajarshi Dasgupta (Journal of Cross Knowledge, 2024)
Personality is an individual's characteristics which are distinguishing characteristics that distinguish that individual from other people. The characteristics mentioned here are internal, namely related to feelings, emotions and characteristics that influence a person's behavior. So far, most teachers do not realize that the character they display in front of their students has a significant influence on their own personality development. Teachers tend to only carry out their main task of teaching, without paying attention to whether what they do is seen, heard and imitated by their students. The purpose of this article is to examine the personality issues of teachers who are role models for students. This study is a literature search that brings together various sources and literature on the topic being discussed